Pathophysiology of oropharyngeal dysphagia in the frail elderly - Rofes, L.; Arreola, V.; Romea, M.; Palomera, E.; Almirall, J.; Cabré, M.; Serra‐prat, M.; Clavé, P. (Neurogastroenterology and motility, 2010)
Background  Oropharyngeal dysphagia is a major complaint among the elderly. Our aim was to assess the pathophysiology of oropharyngeal dysphagia in frail elderly patients (FEP). Methods  A total of 45 FEP (81.5 ± 1.1 years) with oropharyngeal dysphagia and 12 healthy volunteers (HV, 40 ± 2.4 years) were studied using videofluoroscopy. Each subject’s clinical records, signs of safety and efficacy of swallow, timing of swallow response, hyoid motion and tongue bolus propulsion forces were assessed. Key Results  Healthy volunteers presented a safe and efficacious swallow, faster laryngeal closure (0.157 ± 0.013 s) upper esophageal sphincter opening (0.200 ± 0.011 s), and maximal vertical hyoid motion (0.310 ± 0.048 s), and stronger tongue propulsion forces (22.16 ± 2.54 mN) than FEP. By contrast, 63.63% of FEP presented oropharyngeal residue, 57.10%, laryngeal penetration and 17.14%, tracheobronchial aspiration. Frail elderly patients with impaired swallow safety showed delayed laryngeal vestibule (LV) closure (0.476 ± 0.047 s), similar bolus propulsion forces, poor functional capacity and higher 1‐year mortality rates (51.7%vs 13.3%, P = 0.021) than FEP with safe swallow. Frail elderly patients with oropharyngeal residue showed impaired tongue propulsion (9.00 ± 0.10 mN), delayed maximal vertical hyoid motion (0.612 ± 0.071 s) and higher (56.0%vs 15.8%, P = 0.012) 1‐year mortality rates than those with efficient swallow. Conclusion & Inferences  Frail elderly patients with oropharyngeal dysphagia presented poor outcome and high mortality rates. Impaired safety of deglutition and aspirations are mainly caused by delayed LV closure. Impaired efficacy and residue are mainly related to weak tongue bolus propulsion forces and slow hyoid motion. Treatment of dysphagia in FEP should be targeted to improve these critical events.